Comparing Assisted Reproductive Outcomes in Women with Different Polycystic Ovary Syndrome Phenotypes Undergoing Frozen Embryo Transfer - Anubhuti Patel; Anviti Saraf; Vyshnavi A. Rao; Kamini A. Rao (Journal of Human Reproductive Sciences)
Background: Patients with polycystic ovarian syndrome (PCOS) have unique characteristics depending on its phenotype. Therefore, prediction of controlled ovarian stimulation (COS) response and assisted reproductive technique (ART) outcome in these becomes challenging. Aims: To assess the outcomes of assisted reproductive technology (ART) in various polycystic ovary syndrome (PCOS) phenotypes and to evaluate the predictive value of anti-Mullerian hormone (AMH) and total testosterone on ART success. Clinical pregnancy rate (CPR) was measured as the primary outcome. Settings and Design: This was a prospective observational study conducted at a tertiary care centre. Materials and Methods: A total of 190 infertile women with PCOS (Rotterdam criteria) were enrolled and were subdivided into four phenotypes. Baseline screening and transvaginal scan were done. All patients underwent COS using antagonist protocol with recombinant follicle-stimulating hormone, and an agonist trigger was given for follicular maturation. One or two blastocysts were transferred in a frozen–thawed embryo transfer cycle. Luteal phase support was given with vaginal progesterone. Statistical Analysis Used: For quantitative variables, we employed the Kruskal-Wallis Test with post hoc Tukey’s analysis. For continuous or ordinal variables, the Mann-Whitney U test was utilized. The analysis of categorical data was conducted using the Chi-square (χ2) test with SPSS 21 software. Results: Phenotype A was the most prevalent (37%). CPR was the highest in phenotype D (57.7%), followed by phenotype C (53.06%), A (43%) and B (36%). The mean serum AMH level was the highest in phenotype A (9.7 ± 4.3 ng/dL) and the lowest in phenotype B (5.9 ± 1.8 ng/dL). The mean total testosterone level was 103 ± 15.68 ng/mL in Type A, 109.46 ± 37.08 ng/mL in Type B and 48.52 ± 17.07 ng/ml in Type D. Conclusion: Phenotype D showed higher CPR and lower miscarriage rate compared to other phenotypes (not significant) and was associated with good clinical outcome. No correlation could be established with serum AMH, total testosterone levels and CPR.